Perancangan Sistem Otomatisasi On/Off Penerangan Lampu LED E-14 Bebasis Internet Of Things (IOT) Menggunakan Mikrokontroler Node MCU ESP 6288 Dan Android System (Telegram Bot.) - Sumaedi, Ade; Widodo, Amin; Rohwanah, Rohwanah; Yudhistira, Yudhistira (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2024)
The On/Off system for lighting in general is still manual, namely the process of turning it off and on still using a switch, where the process takes a long time and requires energy to work on. From these problems, researchers take advantage of the development of the internet/Wi-Fi and the Android system to create an automation system that is fast, precise, and accessible from anywhere and anytime. In this case, the solution to this problem is to develop a prototype design for On/Off automation of LED-E14 lighting based on the Internet of Things (IoT) which makes it easier for humans to carry out all their activities. The research method carried out is starting from designing the physical form of the system or hardware system using the NodeMCU 8266 microcontroller which is connected to the internet network using the Arduino IDE software programming. The results of the research on the design of the On/Off automation system for E-14 LED lighting are designed starting from the On/Off program for lights and telegram bots that have been made (coding system) then transferred to the NodeMCU 8266 microcontroller, where the NodeMCU 8266 microcontroller is given electricity using a cellphone charger (micro electricity) which is connected to the Relay Module 4 Channel, the electricity is transferred to 4 E-14 LED lights, namely with several commands from telegram (Android System) using internet/wifi. The design of this IoT technology can be developed to be implemented in the manufacturing industry, offices, etc.